PENGARUH PEMBERIAN SLUDGE DALAM RANSUM PAKAN TERHADAP LAJU PERTUMBUHAN BENIH IKAN NILA GIFT (Oreochromis sp.) - Rustidja Rustidja (Jurnal Perikanan Universitas Gadjah Mada, 2003)
The aim of the study was to know the effect of sludge as the waste of biogas in the feed ration on the growth of nile(Oreochromis sp.) fingerling.The design experiment used in this experiment was Completely Randomized Design with 4 tretments namely 10; 20; 30; and 40% of sludge ration. A commercial fish feed used as the control. The treatments were done in triplicate.The result showed that the additions of sludge in each ration did not affect all growth parameter observed, suggesting sludge might be added to the ration up to 40%. The Survival Rates, Specific Growth Rates, Feed Conversion Ratios (FCR), Net Protein Utilization (NPU), EneryConvertion Efficiency (ECE), Protein Efficiency Ratios (PER) ranged from 94,8 to 94,27, 4,77 to 5,98% BW/day, 0,71 to 1,18, 39,3 to 58,97%, 26,45 to 41,49%, and 2,71 to 4,5, respectivey.